A control for the day‐to‐day normalization of the flow cytometry γ‐H2AX assay for clinical routine. Issue 6 (27th February 2018) - Viktorisson, Adam; Mathew, Sherin T.; Hammarsten, Ola; Johansson, Pegah
Abstract : Background: The phosphorylation of histone H2AX (γ‐H2AX) at the DNA double‐strand break (DSB) site is frequently used for quantifying DSBs and may be useful as a biomarker for clinical applications. We have previously reported a flow cytometry‐based quantification of γ‐H2AX for clinical routine. One major challenge, however, is the lack of a control sample for normalization of the day‐to‐day variation of the flow cytometry γ‐H2AX assay. Methods: Here, we report development of a mix‐control sample containing peripheral blood mononuclear cells (PBMC) from 10 control individuals, for normalization of day‐to‐day variation of the flow cytometry‐γ‐H2AX assay. Results: We showed that control individuals sampled on different days show an average day‐to‐day variation (CV) of 34%, which was reduced to 12% after normalization to the control sample. The normalization allowed detection of radiosensitivity of lymphoblastoid cell lines from ataxia telangiectasia patients, sampled over three days. Conclusion: The mix‐control sample, consisting of 10 control individuals' PBMC, can be used as a control sample to normalize for day‐to‐day variation of the γ‐H2AX assay. The use of this sample will facilitate integration of the γ‐H2AX assay into clinical routine. © 2018 International Clinical Cytometry Society